A Diameter Distribution Yield Prediction for Teak Stands in Taungoo District, Bago Region of Myanmar - Naing, Yan Myo (Open Science Journal, 2020)
A parameter recovery procedure was applied to characterize the parameters for the Weibull distribution function based on four percentile methods and two hybrid methods which were the combination of diameter percentiles and moment methods. The procedure was used to develop a diameter distribution yield prediction for teak stands in Taungoo District of Myanmar. All the methods were evaluated by using independent observed data and calculating error indices. Among them, method 1 which involved the 31st and 63rd diameter percentiles produced the lowest error index. Therefore, method 1 was considered to predict yield based on diameter distribution and selected to construct a yield table for the study area. An example was also provided to show users how to apply this kind of yield prediction.